Aplikasi Pembelajaran Matematika “PIJAR Berbasis Web Menggunakan Model ADDIE Di SMPN 1 Punggelan - Dwi Anasrulloh; Heni Rahmawati; Luthfi Nur Azizah (CV. ITTC INDONESIA, 2025)
This study aims to develop a web-based mathematics learning application called PIJAR (Interactive Learning of Spatial Architecture) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. This application focuses on eighth-grade junior high school geometry material covering the Pythagorean Theorem, Circles, and Flat-Sided Spatial Figures. The research used the Research and Development (R&D) method with data collection techniques through observation, interviews, and questionnaires. The results showed that the PIJAR application was successfully designed and implemented according to the learning needs at SMPN 1 Punggelan. Based on tests by subject matter experts, media experts, and student responses, the application was deemed highly suitable for use because it is able to present interactive material, practice questions, and automatic evaluations that make it easier for students to understand geometric concepts. Thus, the PIJAR application can be an innovative solution in improving the quality of mathematics learning and providing an independent and interesting learning experience for junior high school students.